Pyrolysis for plastic waste: Environmental goals vs business interests, which is more realistic? - Muji Setiyo; Sunaryo Sunaryo; Muhammad Latifur Rochman (Mechanical Engineering for Society and Industry, 2025)
Global plastic production exceeds 390 million tons annually, yet only about 9% is recycled, leaving severe environmental impacts. Pyrolysis is emerging as a promising solution, converting plastic waste into fuels and chemicals. However, popular claims on mass media and commercial technology publications, that 1 kg of plastic yields 1 liter of fuel are misleading, as they ignore differences in mass, volume, and fuel density. Pyrolysis oil can indeed serve as fuel but often needs further refining to meet engine standards. Economically, it holds potential, with oil prices ranging from USD 600–900 per ton and syngas generating up to 800 kWh per ton. Nonetheless, high capital and operational costs challenge its feasibility, particularly for small-scale operations. Environmentally, pyrolysis aligns with sustainability and circular economy goals, potentially reducing emissions by up to 3.5 tons of CO₂-equivalent per ton of plastic processed. This paper examines pyrolysis critically, addressing misconceptions and evaluating its realistic prospects as both an environmental solution and a business venture.